2006
DOI: 10.1586/1744666x.2.3.419
|View full text |Cite
|
Sign up to set email alerts
|

Insulin: a critical autoantigen and potential therapeutic agent in Type 1 diabetes

Abstract: Insulin is a polypeptide hormone secreted by pancreatic beta-cells and is critical for glucose homeostasis. Abnormalities in insulin secretion result in various forms of diabetes. Type 1A diabetes is an autoimmune form in which insulin has been identified as a critical autoantigen. Recent studies have identified genetic determinants of insulin-specific autoimmune responses and insulin epitopes targeted by autoreactive T lymphocytes. The study of insulin as an autoantigen has also led to discoveries about basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…Thus, what may ultimately be critical in developing robust long lasting tolerance is induction of autoantigen specific Tregs where low-dose IL-2 may help to increase their numbers. A clinical trial in patients with T1D, who by necessity immunize themselves with a key autoantigen, insulin [126], on a daily basis, present a unique opportunity to test this concept and may be relevant to other autoimmune diseases. Lastly, IL-2 exhibits poor pharmacokinetic with very short-half life in the blood, approximately 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, what may ultimately be critical in developing robust long lasting tolerance is induction of autoantigen specific Tregs where low-dose IL-2 may help to increase their numbers. A clinical trial in patients with T1D, who by necessity immunize themselves with a key autoantigen, insulin [126], on a daily basis, present a unique opportunity to test this concept and may be relevant to other autoimmune diseases. Lastly, IL-2 exhibits poor pharmacokinetic with very short-half life in the blood, approximately 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that this is the case for insulin. In man, insulin expression in the thymus is influenced by allelic variation and epigenetic regulation of the insulin gene [40, 41], noting that this has been identified as a susceptibility locus for T1D and insulin is a key autoantigen [42, 43]. We also showed that other T1D autoantigens, such as IA-2 and IGRP, exist in several spliced variants with different expression patterns in human pancreas and thymus, suggesting that self-tolerance may not be achievable to epitopes expressed only by the pancreas [4447].…”
Section: Type 1 Diabetes: An Autoimmune Disease With Chronic Immune Dmentioning
confidence: 99%
“…Alternative splicing of Deaf1 may be caused by inflammation, which in turn impairs expression of the eukaryotic translation initiation factor 4 gamma 3 (Eif4g3) [43]. These studies illustrate molecular events that may result in lower expression of self-molecules (e.g., insulin, an autoantigen in T1D) [63] and impaired induction of peripheral tolerance at a site that is believed to be key to the regulation and activation of islet autoimmune responses, the pancreatic lymph node. nPOD also supported studies that provided a more in-depth phenotypic analysis of cells that express self-molecules in peripheral lymphoid tissues, in particular extra-thymic Aire -expressing cells [64] that are now known to represent a bone marrow-derived, distinct phenotype with similarities to dendritic cells [46•].…”
Section: Introductionmentioning
confidence: 99%